Characteristics of Immobilized Urease on Grafted Alginate Bead Systems - Danial,Enas N. (2015)
This study evaluated the biological importance of immobilized urease enzyme over the free urease. The support material used for urease immobilization was alginate. Generally, the immobilization of urease in alginate gel showed a marked increase in Km and Vmax. However, the immobilized urease showed higher thermal stability than that of free enzyme. The rate of thermal inactivation of the immobilized enzyme decreased due to entrapment in gel matrix. Also, the activity of the immobilized urease was more stable in retention than that of the free enzyme during the storage in solution, although the activity of the immobilized enzyme was lower in comparison with the free enzyme. A stable immobilized system and long storage life are convenient for applications that would not be feasible with a soluble enzyme system. These results highlighted the technical and biochemical benefits of immobilized urease over the free enzyme.